AN EVALUATION OF THE EXTENT SECONDARY SCHOOLS IN ZIMBABWE SENSITISE PUPILS ON SEXUAL AND REPRODUCTIVE HEALTH ISSUES. - Ruparanganda, Fenton (IJRDO- Journal of Educational Research, 2017)
This study sought to find out the extent to which the schools help in sensitizing secondary school pupils on sexual and reproductive health issues. The research was carried out in Chimanimani district in Zimbabwe which is an agrobased area with severals farms .It is characterized by high prevalence of HIV/AIDS and other diseases of the reproductive system. A purposive sample of three schools was used; these were the only schools offering biology and located in farming areas where the human population is vey high and is hard hit by HIV. A blend of qualitative and quantitative research methods was used. The data was collected from biology teachers and biology students through questionnaires, interviews, and lesson observation. The extent to which the school curriculum helps in raising pupils’ awareness was determined by examining the teachers’ knowledge, skills and attitudes towards sexual and reproductive health issues, analyzing the teaching methods, teaching aids, material available and then pupils’ knowledge on sexual and reproductive health issues. Most teachers in this research had little knowledge about sexual and reproductive health issues that are not a result of an infection for example endometriosis, prostate carcinomas and fibroids. The biology syllabus does not address majority of the aspects it focuses on a narrow range of issues. Students indicated that the curriculum helps them to understand other issues but it does not address real life skills required to manage certain issues like menstruation and students have pointed out that some of the knowledge about other sexual and reproductive health issues is from their peers.Teachers and parent do not discuss openly with secondary school students sexual and health issues.